A comprehensive review in incremental forming on approaches of deformation analysis and surface morphologies. (2021) - Pratheesh Kumar, S.; Elangovan, S.; Mohanraj, R.; Boopathi, S.
Abstract: Incremental forming is an effective way of manufacturing the part with customized geometry to the end user. The flexible deformation of sheet is the effect of tool squeeze and traverse over strategic paths with significant increment in step depth. The formability is mainly dependent on localized plastic-deformation of blank, ensures that validation of deformation stability, linear wall strain distribution and material characteristics. This review article begins with deformation analysis and discusses the influential factors and ends-up with surface integrity. Reviewing various research articles based on deformation mechanism expresses the various outlines such as texture evolution, transition of plane-strain mode in both SPIF and DSIF samples. These discussions provide the enlarged view of the current research gap and establish a strong perspective to industrial applications.